2016
DOI: 10.11131/2016/101199
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic Receptor-Mediated Regulation of Intestinal Barrier Function and Innate Immunity

Abstract: The molecular basis for the regulation of the intestinal barrier is a very fertile research area. A growing body of knowledge supports the targeting of various components of intestinal barrier function as means to treat a variety of diseases, including the inflammatory bowel diseases. Herein, we will summarize the current state of knowledge of key xenobiotic receptor regulators of barrier function, highlighting recent advances, such that the field and its future are succinctly reviewed. We posit that these rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 215 publications
(234 reference statements)
0
36
0
Order By: Relevance
“…However, these receptors can also act as important regulators of inflammation and immunity, especially in the intestine. 27,[39][40][41] The PXR, a master regulator of the human drug metabolism enzyme CYP3A4 (CYP3A11 in mice), is expressed throughout the intestine and liver where it can "sense" endogenous and exogenous substances. At these sites, activation of the PXR can also exert anti-inflammatory and pro-healing effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, these receptors can also act as important regulators of inflammation and immunity, especially in the intestine. 27,[39][40][41] The PXR, a master regulator of the human drug metabolism enzyme CYP3A4 (CYP3A11 in mice), is expressed throughout the intestine and liver where it can "sense" endogenous and exogenous substances. At these sites, activation of the PXR can also exert anti-inflammatory and pro-healing effects.…”
Section: Discussionmentioning
confidence: 99%
“…IPA and IAA are proposed as beneficial indole derivatives produced by desirable genera within the gut microbiome (40,53). Studies have correlated IPA and IAA levels with better prognosis for individuals with type 2 diabetes, Crohn's disease, and inflammatory bowel disease (49,(52)(53)(54)(55). IPA was also in clinical trials for its effect against Alzheimer's disease (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, these same derivatives act, via an unknown mechanism, as antibacterials against Legionella pneumophila (44)(45)(46) and Mycobacterium tuberculosis (47,48), and possess antiinflammatory properties (40,(49)(50)(51). High levels of these indole derivatives in peripheral circulation correlate with protection against inflammatory bowel disease, Crohn's disease, and type 2 diabetes (49,(52)(53)(54)(55); one of them was in clinical trials as an antiinflammatory that reduces Alzheimer's disease progression (56,57).…”
Section: Significancementioning
confidence: 99%
“…We have previously shown that PXR activation down-regulates TLR4 mRNA expression leading to inhibition of NF-κB signaling 2,35,36 . We have also shown that FKK5 and FKK6 interact directly with PXR LBD and result in its activation.…”
Section: Characterization Of Fkk5 and Fkk6 On Pxr-tlr4 And Nf-κb Signmentioning
confidence: 99%
“…We have also shown that FKK5 and FKK6 interact directly with PXR LBD and result in its activation. Thus, to determine the effect of FKK5 and FKK6 on the PXR-TLR4-NF-κB signaling pathway, we used PXR-transfected Caco-2 cells and exposed these cells to FKK5 and 6 since undifferentiated Caco-2 cells inherently have low PXR expression (not detected) but relatively higher TLR4 expression and are excellent in vitro models for the study of enterocyte function [36][37][38][39] . FKK5 and FKK6 down-regulates TLR4 (0.39-fold and 0.49-fold, respectively) but up-regulates CYP3A4 (3.7-fold and 3.29-fold, respectively) and MDR1 (5.12-fold and 6.45-fold, respectively) mRNA expression ( Fig.…”
Section: Characterization Of Fkk5 and Fkk6 On Pxr-tlr4 And Nf-κb Signmentioning
confidence: 99%